Pengembangan Buku Saku Interaktif Tentang Etika Berinteraksi Dalam Islam Di Era Digital - Wannur, Zaim; Zuliana, Zuliana (EL-EMIR Institute, 2024)
This study aims to develop an interactive pocket book on ethics of interaction in Islam in the digital era that can be used as an innovative learning medium for students. This pocket book is designed to help students understand the values ​​of Islamic ethics in communicating and interacting through digital media, while encouraging them to apply these values ​​in their daily lives. The research method used is the research and development method (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research process begins with a needs analysis through literature reviews and interviews with teachers and students, then continues with the design of the content and design of the pocket book. The development of the pocket book is carried out based on the principles of interactivity and relevance of the material. Evaluation is carried out through product trials on a number of students and teachers to obtain feedback on the quality of the pocket book, both in terms of content, design, and ease of use. The results of the study show that the interactive pocket book developed is effective and attractive to students. This book contains material on the principles of Islamic ethics, such as honesty, politeness, responsibility, and maintaining honor, which are associated with the practice of interaction in the digital world. The responses of students and teachers to this pocket book were very positive, with an average score of the product validation assessment in the